Analisis Konsumsi Bahan Bakar Dan Emisi Karbon Dioksida (CO2) Pada PLTDG Blok 2 di PT. Indonesia Power UP Bali - I Wayan Sutama; Kadek Jodi Mustika; I Wayan Suriana (Universitas Pendidikan Nasional, 2022)
This study contains an electric power system consisting of generation, distribution and distribution. One type of power plant is a Gas Diesel Power Plant (PLTDG). As industrial activities and population increase, the demand for electrical power also increases. This results in each generator having to be effective and maximum so as not to cause losses, the generator must also be environmentally friendly so as not to cause global warming. Where the effect of specific fuel consumption and load percentage greatly affects thermal efficiency, as well as the amount of fuel consumption greatly affects the economy and CO2 emissions generated at the power plant. Therefore, it is important to know the efficiency from an economic point of view, the performance of the PLTDG power plant and the resulting CO2 emissions. One of the efforts made is by changing the main fuel for the generator. The results of the analysis show that using LNG fuel thermal efficiency, electricity costs per kWh and the resulting emissions are better than using HSD fuel.